Detection of Uncoupled Circadian Rhythms in Individual Cells of Lemna minor using a Dual-Color Bioluminescence Monitoring System. (9th March 2021) - Watanabe, Emiri; Isoda, Minako; Muranaka, Tomoaki; Ito, Shogo; Oyama, Tokitaka
Abstract: The plant circadian oscillation system is based on the circadian clock of individual cells. Circadian behavior of cells has been observed by monitoring the circadian reporter activity, such as bioluminescence of AtCCA1::LUC+ . To deeply analyze different circadian behaviors in individual cells, we developed the dual-color bioluminescence monitoring system that automatically measured the luminescence of two luciferase reporters simultaneously at a single-cell level. We selected a yellow-green-emitting firefly luciferase (LUC+) and a red-emitting luciferase (PtRLUC) that is a mutant form of Brazilian click beetle ELUC. We used AtCCA1::LUC+ and CaMV35S::PtRLUC. CaMV35S::LUC+ was previously reported as a circadian reporter with a low-amplitude rhythm. These bioluminescent reporters were introduced into the cells of a duckweed, Lemna minor, by particle bombardment. Time series of the bioluminescence of individual cells in a frond were obtained using a dual-color bioluminescence monitoring system with a green-pass- and red-pass filter. Luminescence intensities from the LUC+ and PtRLUC of each cell were calculated from the filtered luminescence intensities. We succeeded in reconstructing the bioluminescence behaviors of AtCCA1::LUC+ and CaMV35S::PtRLUC in the same cells. Under prolonged constant light conditions, AtCCA1::LUC+ showed a robust circadian rhythm in individual cells in an asynchronous state in the frond, as previously reported. By contrast, CaMV35S::PtRLUC stochastically showed circadian rhythms in a synchronous state. These results strongly suggested the uncoupling of cellular behavior between these circadian reporters. This dual-color bioluminescence monitoring system is a powerful tool to analyze various stochastic phenomena accompanying large cell-to-cell variation in gene expression.